The Relationship Between Work Motivation and Teacher Performance in the Islamic Education Environment - Emeliazola, Emeliazola; Sesmiarni, Zulfani (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2024)
The aim of this research is to explore and analyze the relationship between work motivation and teacher performance in the Islamic educational environment. This research aims to identify dimensions and indicators of work motivation that significantly influence teacher performance, as well as understand the extent to which factors such as compensation, working conditions, and organizational support contribute to teacher work motivation. The research method used in this research is a correlational quantitative method to examine the relationship between work motivation and teacher performance at MTSN 1 Bukittinggi City. The results of this research show that there is a significant but negative relationship between work motivation and teacher performance at MTsN 1 Bukittinggi City, with a moderate level of relationship. Although work motivation is generally considered important for improving performance, these results show that other factors also play a significant role in determining teacher performance. Therefore, school management is advised to adopt a more holistic and comprehensive approach in managing human resources in order to create a work environment that supports and improves overall teacher performance. Further research is needed to explore causal relationships and other factors that influence teacher performance and develop more effective strategies in increasing work motivation and teacher performance.